PENERAPAN INTERVENSI MINDFULL THERAPY DALAM ASUHAN KEPERAWATAN PADA KLIEN DENGAN MASALAH ANSIETAS - Leni Wijaya; Rusmala Dewi (LPPM STIKes Mitra Adiguna, 2026)
Anxiety is a psychological disorder commonly experienced by older adults, particularly those living in social institutions due to environmental changes, loss of social roles, and limited interaction with family members. One non-pharmacological intervention that can be applied by nurses to reduce anxiety is mindfulness therapy. This study aimed to determine the implementation of mindfulness therapy intervention in nursing care for clients with anxiety. The research design used in this study was a one-group pretest–posttest design. The population consisted of 63 older adults residing at Harapan Kita Elderly Social Institution in Palembang. Sampling was conducted using a non-probability sampling method with purposive sampling technique, involving 32 respondents who met the inclusion and exclusion criteria. Data analysis was performed using univariate and bivariate analysis with the Shapiro–Wilk parametric test. The results showed a p-value of 0.000 (p < 0.05), indicating that mindfulness therapy significantly reduced anxiety levels among older adults. It is recommended that mindfulness therapy be implemented as part of a complementary approach to support the mental health of older adults, applied continuously to help reduce anxiety levels, improve quality of life, and enhance social interaction and daily activities among older adults.